2016
DOI: 10.1049/iet-syb.2015.0090
|View full text |Cite
|
Sign up to set email alerts
|

Protein sequestration versus Hill‐type repression in circadian clock models

Abstract: Circadian (~24hr) clocks are self-sustained endogenous oscillators with which organisms keep track of daily and seasonal time. Circadian clocks frequently rely on interlocked transcriptionaltranslational feedback loops to generate rhythms that are robust against intrinsic and extrinsic perturbations. To investigate the dynamics and mechanisms of the intracellular feedback loops in circadian clocks, a number of mathematical models have been developed. The majority of the models use Hill functions to describe tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(116 citation statements)
references
References 219 publications
(506 reference statements)
8
107
1
Order By: Relevance
“…On the other hand, varying V max leads to a larger change in period but a smaller change in amplitude and period stability than simulations with varying K d (Figure S7A). Similar patterns were also observed when different circadian clock models were used [54, 58, 59] (Figure S7B). …”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…On the other hand, varying V max leads to a larger change in period but a smaller change in amplitude and period stability than simulations with varying K d (Figure S7A). Similar patterns were also observed when different circadian clock models were used [54, 58, 59] (Figure S7B). …”
Section: Resultssupporting
confidence: 78%
“…We have previously used the Kim-Forger circadian model, which describes the core transcriptional-translational negative feedback loop of the circadian clock [14, 54], but uses a simple linear degradation process for PER. Recent studies have shown that a Michaelis-Menten type of degradation can be used to simulate the biological proteasomal degradation involving multiple components such as ubiquitin; E1, E2, and E3 enzymes; deubiquitinases; and the proteasome [55, 56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenous protein levels were determined by immunoblotting and quantitated using the ImageJ software, version 1.45 [NIH software package (40)] or Image Lab Software followed by detection using Gel Doc XR+ System (Bio-Rad). For mathematical modeling, we extended a previous model of the intracellular mammalian circadian clock (24,25) to describe interactions between p53 and Per2 ( Fig. 2 A and D).…”
Section: Methodsmentioning
confidence: 99%
“…2D, Tables S2 and S3, and SI Materials and Methods). First, we modified the Kim and Forger's model used to represent the dynamics of the transcriptional negative arm generated by Per2 (24,25). Second, we considered the ubiquitination status of p53 as it modulates p53 degradation and shuttling (26).…”
Section: Mathematical Modeling Predicts Underlying Interactions Betweenmentioning
confidence: 99%